Advances in Computing : 12th Colombian Conference, CCC 2017, Cali, Colombia, September 19-22, 2017, Proceedings /: 12th Colombian Conference, CCC 2017, Cali, Colombia, September 19-22, 2017, Proceedings. (2017) - Unknown
No abstract available